Traumatic brain injury: a current review of clinical management - Febres Ramos, Richard (2026)
Traumatic brain injury (TBI) is one of the leading causes of death and disability worldwide, predominantly affecting young adults of working age and imposing a substantial social and economic burden. Its impact is greater in low- and middle-income countries such as Peru, where the high incidence of traffic accidents, urban violence, and limitations in healthcare infrastructurecontribute to increased morbidity and mortality. Despite advances in monitoring techniques and clinical and surgical management strategies, TBI continues to pose a complex clinical challenge due to the multifactorial nature of primary injury and the rapid progression of secondary injury. In recent years, advances in the management of TBI have led to the development of prognostic systems that surpass the predictive capacity of traditional scales. In addition to the Glasgow Coma Scale and the Marshall computed tomography (CT) classification, tools such as the Rotterdam CT Score, the IMPACT model, and the Helsinki CT Score have been incorporated. These tools integrate clinical, physiological, and imaging variables to more accurately predict mortality and functional outcomes. They complement clinical judgment and provide essential support for risk stratification and decision–making in neurosurgical emergencies. This article presents a narrative, systematized review of the literature published between 2015 and 2025 in PubMed, Scopus, LILACS, and the Cochrane Library, covering international guidelines, systematic reviews, clinical trials, and observational studies. The main medical management strategies are addressed, such as intracranial pressure control, targeted osmotherapy, anticonvulsant prophylaxis, and hemodynamic optimization, as well as the current indications for the most common surgicalinterventions, including hematoma evacuation and decompressive craniectomy in cases of refractory intracranial hypertension. Recent advances in multimodal monitoring, serum biomarkers, and telemedicine are also reviewed, underscoring the need to adapt international guidelines to the Peruvian context in order to optimize functional outcomes.